Factors influencing motivation level of academic staff in Education of IBA Community College Khairpur Mir's (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
To investigate the degree to which various factors influence motivation level of academic staff of IBA Community College Khairpur Mir's. The study has utilized a questionnaire survey. Participants were 40 (24 male, 16 female) from academic staff. A 21-item questionnaire survey was used that that measured satisfaction level and overall motivation of academic staff. Job satisfaction was measured using five dimensions namely: pay, working conditions, job security, work itself and recognition. To determine its reliability, data was entered in SPSS 16 for checking Cronbach's alpha through correlation analysis then data reduction technique was used to form five factors among all. Two tailed Pearson correlation test was applied for checking the correlation ship among variables.Working condition, recognition and satisfaction level is somehow correlated with work itself.The level of relationship is not too much strong to analyze which factor has high significance and which has low. This study conducted upon college teachers can also be conducted upon university teachers and other sector organizations. The study also declared the factors, which were motivating for the teachers at academic education level. The empirical results from this study would help in describing or clarifying the crucial role of motivation on the needs satisfaction of teachers.